Combined CUTLASS, EISCAT and ESR observations of ionospheric plasma flows at the onset of an isolated substorm - Yeoman, T. K.; Davies, J. A.; Wade, N. M.; Provan, G.; Milan, S. E. (HAL CCSD, 2000)
International audience On August 21st 1998, a sharp southward turning of the IMF, following on from a 20 h period of northward directed magnetic field, resulted in an isolated substorm over northern Scandinavia and Svalbard. A combination of high time resolution and large spatial scale measurements from an array of coherent scatter and incoherent scatter ionospheric radars, ground magnetometers and the Polar UVI imager has allowed the electrodynamics of the impulsive substorm electrojet region during its first few minutes of evolution at the expansion phase onset to be studied in great detail. At the expansion phase onset the substorm onset region is characterised by a strong enhancement of the electron temperature and UV aurora. This poleward expanding auroral structure moves initially at 0.9 km s -1 poleward, finally reaching a latitude of 72.5°. The optical signature expands rapidly westwards at ~6 km s -1 , whilst the eastward edge also expands eastward at ~0.6 km s -1 . Typical flows of 600 m s -1 and conductances of 2 S were measured before the auroral activation, which rapidly changed to ~100 m s -1 and 10-20 S respectively at activation. The initial flow response to the substorm expansion phase onset is a flow suppression, observed up to some 300 km poleward of the initial region of auroral luminosity, imposed over a time scale of less than 10 s. The high conductivity region of the electrojet acts as an obstacle to the flow, resulting in a region of low-electric field, but also low conductivity poleward of the high-conductivity region. Rapid flows are observed at the edge of the high-conductivity region, and subsequently the high flow region develops, flowing around the expanding auroral feature in a direction determined by the flow pattern prevailing before the substorm intensification. The enhanced electron temperatures associated with the substorm-disturbed region extended some 2° further poleward than the UV auroral signature associated with it. Key words: Ionosphere (auroral ionosphere) - ...